2018
DOI: 10.3390/ijms19092592
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin Attenuates Myocardial Hypertrophy Induced by Transverse Aortic Constriction via Oxidative Stress Inhibition and SIRT3 Pathway Enhancement

Abstract: Dihydromyricetin (DMY), one of the flavonoids in vine tea, exerts several pharmacological actions. However, it is not clear whether DMY has a protective effect on pressure overload-induced myocardial hypertrophy. In the present study, male C57BL/6 mice aging 8–10 weeks were subjected to transverse aortic constriction (TAC) surgery after 2 weeks of DMY (250 mg/kg/day) intragastric administration. DMY was given for another 2 weeks after surgery. Blood pressure, myocardial structure, cardiomyocyte cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 58 publications
2
39
0
Order By: Relevance
“…Histopathological changes were assessed by a light microscope at 200× magnification (Nikon, Tokyo, Japan). The cardiomyocyte cross-sectional areas were determined by testing the circumferential length of the cardiomyocyte using ImageJ software as described previously (Chen et al, 2018).…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%
“…Histopathological changes were assessed by a light microscope at 200× magnification (Nikon, Tokyo, Japan). The cardiomyocyte cross-sectional areas were determined by testing the circumferential length of the cardiomyocyte using ImageJ software as described previously (Chen et al, 2018).…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%
“…BZP exhibits potent neuroprotective effects against ischaemic stroke, which may be related to its antioxidative effects and inhibition of apoptosis . As is well‐known, autophagy can be induced by oxidative stress, and antioxidants play a protective role in pressure overload‐induced cardiac hypertrophy . Besides, an increasing number of studies have revealed that crosstalk exists between autophagic and apoptotic machinery .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity recommended. In addition, although existing research reports show that the expression level of the sirtuin protein is consistent with the change in activity level [85][86][87], the activity of sirtuins in diabetic lung tissue needed to be detected for further study. Second, we did not investigate the specific mechanisms of MSCs on diabetic lung fibrosis that is composed of nearly 40 different cell types in vitro.…”
mentioning
confidence: 95%